Staff Studies for the World Economic Outlook. (World Economic and Financial Surveys; World Economic and Financial Surveys, 1995)
These studies, prepared by the staff of the International Monetary Fund, comprise supporting material for the analyses and scenarios in the World Economic Outlook and provide a more detailed examination of the theory and evidence on some major issues affecting the global economy, commodity prices, and individual countries.